2012
DOI: 10.1186/1472-6750-12-95
|View full text |Cite
|
Sign up to set email alerts
|

Use of anionic denaturing detergents to purify insoluble proteins after overexpression

Abstract: BackgroundMany proteins form insoluble protein aggregates, called “inclusion bodies”, when overexpressed in E. coli. This is the biggest obstacle in biotechnology. Ever since the reversible denaturation of proteins by chaotropic agents such as urea or guanidinium hydrochloride had been shown, these compounds were predominantly used to dissolve inclusion bodies. Other denaturants exist but have received much less attention in protein purification. While the anionic, denaturing detergent sodiumdodecylsulphate (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 22 publications
0
39
0
1
Order By: Relevance
“…Expression and purification of Mce4A was done successfully with the help of earlier published protocol [6,24] with slight modifications which yields sufficient amount of the protein. The purity of the purified Mce4A was checked through SDS-PAGE and western blotting by using anti-His tag monoclonal antibody.…”
Section: Expression and Purification Of Mce4amentioning
confidence: 99%
See 1 more Smart Citation
“…Expression and purification of Mce4A was done successfully with the help of earlier published protocol [6,24] with slight modifications which yields sufficient amount of the protein. The purity of the purified Mce4A was checked through SDS-PAGE and western blotting by using anti-His tag monoclonal antibody.…”
Section: Expression and Purification Of Mce4amentioning
confidence: 99%
“…The cultures were grown for next three hours and the cells were harvested by centrifugation at 5000 rpm for 20 minutes, supernatant was discarded and the pellets were collected. Purification was performed by published protocol with slight modification[19]. These pellets were dissolved in cell lysis buffer (cell lysis buffer contained8 mM Na 2 HPO 4 , 286 mM NaCl, 1.4 mM KH 2 PO 4 , 2.6 mM KCl and 1% SDS (w/v) at pH 7.4) for 15 minutes to make cell lysate homogeniesed.…”
mentioning
confidence: 99%
“…For B. subtilis CotB, 1% SDS was added to the lysis buffer to aid in solubilization of the protein (61). The cells were lysed by sonication, followed by chilling to precipitate the SDS.…”
Section: Methodsmentioning
confidence: 99%
“…SDS-PAGE (Figure 1), western blot and protease assay have showed that seven out of twelve recombinant proteases were insoluble form, whilst another five enzymes were not expressed. The major problem in protein expression would be the formation of "inclusion bodies" that occur when the heterologous protein overexpressed [30]. The insoluble protein could be formed by the association of partially folded protein or misfolded protein [31].…”
Section: Resultsmentioning
confidence: 99%